Variabilita osy páteře ve frontální rovině ve vztahu k proměnlivosti parametrů chodidel na tlakové plošině u florbalistů - Odstrčilová, Markéta (Vysoké učení technické v Brně. CESA, 2025)
Tato Bakalářská práce obsahuje metodiku pro pozorování variability osy páteře ve frontální rovině ve vztahu k proměnlivosti parametrů chodidel na tlakové plošině u florbalistů. V teoretické části práce jsou popsány anatomie vybraných částí lidského těla, svalové řetězce podle Myerse a technologie měření pomocí přístroje DIERS. Praktická část obsahuje charakteristiku měřené skupiny, kazuistiku vybraného probanda a diskuzi o naměřených hodnotách.

This bachelor thesis presents a methodology for observing the variability of the spinal axis in the frontal plane in relation to the variability of foot parameters on the pressure platform in floorball players. The theoretical part of the thesis describes the anatomy of selected parts of the human body, muscle chains according to Myers and the measurement technology using the DIERS instrument. The practical part includes the characteristics of the measured group, a case study of the selected proband and a discussion of the measured values.
Variability of the spine axis in the frontal plane in relation to the variability of the parameters of the feet on the pedoscan of floorball players
Keywords: Páteř; skolióza; chodidla; DIERS; Spine; scoliosis; feet; DIERS